Extracorporeal shock waves as curative therapy for varicose veins? - Fiorenzo Angehrn (Dove Medical Press, 2008)
Fiorenzo Angehrn1, Christoph Kuhn1, Ortrud Sonnabend2, Axel Voss31Klinik Piano, Biel, Switzerland; 2Pathodiagnostics, Herisau, Switzerland; 3SwiTech Medical AG, Kreuzlingen, SwitzerlandAbstract: In this prospective design study the effects of low-energy partially focused extracorporeal generated shock waves (ESW) onto a subcutaneous located varicose vein – left vena saphena magna (VSM) – are investigated. The treatment consisted of 4 ESW applications within 21 days. The varicose VSM of both sides were removed by surgery, and samples analyzed comparing the treated and untreated by means of histopathology. No damage to the treated varicose vein in particular and no mechanical destruction to the varicose vein’s wall could be demonstrated. However, an induction of neo-collagenogenesis was observed. The thickness of the varicose vein’s wall increased. Optimization of critical application parameters by investigating a larger number of patients may turn ESW into a non-invasive curative varicose treatment.Keywords: curative therapy, extra-cellular matrix (ECM), histopathologic changes of varicose veins, extracorporeal shock wave (ESW), progenitor cells